Integrated Simulation Challenges with the DeepWind Floating Vertical Axis Wind Turbine Concept. (2015) - Verelst, David; Madsen, Helge A.; Borg, Michael; Paulsen, Uwe Schmidt; Svendsen, Harald G.; Berthelsen, Petter Andreas
Abstract: This paper presents the experiences and challenges with concurrently carrying out numerical model development, integrated simulations and design of a novel floating vertical axis wind turbine, the DeepWind concept. The floating VAWT modelling capabilities of the aero-hydro-elastic HAWC2 simulation tool are briefly described and the design approach adopted for such a challenging project was to independently design subsystems in parallel, apart from essential design specifications. Instability issues encountered when integrating all subsystems in the unified numerical model, in particular blade edgewise and controller instabilities, are presented and efforts to alleviate such issues are detailed. A multidisciplinary design and optimization approach is proposed to eliminate these issues and accelerate future design cycles.